2012
DOI: 10.1603/ec11308
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Metabolic Stress Disinfection and Disinfestation Components to Control <I>Pseudococcus longispinus</I>

Abstract: Metabolic stress disinfection and disinfestation (MSDD) has been demonstrated to effectively control longtailed mealybug, Pseudococcus longispinus (Targioni Tozzetti). Standard components previously used for testing MSDD system included a 30-min physical phase of short cycles pressure changes followed by a 60-min chemical phase using ethanol vapor at 10 kPa. This study investigated the effect of varying the following MSDD components on mealybug mortality: duration of the physical and chemical phases, ethanol c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Assessing the viability of immobile organisms usually involves either maintaining them in the laboratory to observe whether or not they continue their development (Zettler et al 2002, Johnson and, observing their response to physical stimulation (Follett 2004, Zulhendri et al 2012, or assessing their turgidity (Barak et al 2009, Morse et al 2009), color (Hara et al 1993), or both (Whiting et al 1998). These approaches have limitations because laboratory rearing is slow and sometimes complex, and morphological assessments require signiÞcant technical skill and time, and can be subjective.…”
mentioning
confidence: 99%
“…Assessing the viability of immobile organisms usually involves either maintaining them in the laboratory to observe whether or not they continue their development (Zettler et al 2002, Johnson and, observing their response to physical stimulation (Follett 2004, Zulhendri et al 2012, or assessing their turgidity (Barak et al 2009, Morse et al 2009), color (Hara et al 1993), or both (Whiting et al 1998). These approaches have limitations because laboratory rearing is slow and sometimes complex, and morphological assessments require signiÞcant technical skill and time, and can be subjective.…”
mentioning
confidence: 99%
“…Cycles of expansion and compression (physical phase), in combination with low vapour concentrations of ethanol applied with vacuum (chemical phase), were used to kill arthropods and pathogens. Similar research in New Zealand showed that both the physical and chemical (ethanol) phases were required to ensure high mortality of pests (Zulhendri 2012;Zulhendri et al 2012a;Zulhendri et al 2012b).…”
Section: Figurementioning
confidence: 96%
“…In this technique, insects, mites, and other biological pests are exposed to rapid compression, and decompression cycles in combination with atmosphere modification and ethanol vapors or any GRAS identified chemicals. It is a rapid quarantine level method that has physical and chemical phases providing biostatic and biocidal effects (Lagunas‐Solar, Essert, Piña, Zeng, & Truong, 2006; Zulhendri, De Silva, et al., 2012). This system and method were patented to Lagunas Solar and Essert (2011).…”
Section: Emerging Technologiesmentioning
confidence: 99%
“…Mortality is achieved by cyclic anoxia environment by lowering oxygen concentration and increasing the amount of carbon dioxide, causing the metabolic arrest to the insects, and thereby, hypoxia toxicity occurs. Ethanol is responsible for disrupting and disorganizing phospholipid bilayer of the cell membrane and also affects ATP production by interrupting potassium ions‐stimulated p‐nitrophenyl phosphatase activity (Zulhendri, De Silva, et al., 2012).…”
Section: Emerging Technologiesmentioning
confidence: 99%